Editorial: Review of the Aims and Scope of Jurnal Psikologi - Pertiwi, Pradytia Putri (Jurnal Psikologi, 2024)
The editorial team of Jurnal Psikologi is excited to announce the renewal of our aims and scope to include emerging areas of psychological research, while reinforcing our commitment to the study of Indonesian psychology. The revised aims and scope offer a more precise and direct focus on understanding the unique ways cultural, social, environmental, and technological influences shape the mental processes and behavior of Indonesians. These insights can be presented in the form of original research and review articles, as we recognize that human knowledge can flourish and advance thanks to the empirical results reported in original research, while reviews help to refine our awareness of important subjects. In highlighting the unique psychological landscape of Indonesia, our goal is to enrich the psychological research based on Indonesians’ vast and diverse characteristics, enabling both local and global society to discover an in-depth understanding and empathetic utilization of the information. We are especially interested in several topics regarding the Indonesian psyche, including the influences of environment, technology, and the digital world. Why? We argue that these aspects play a crucial role in (re)shaping and cementing the psychological landscape of Indonesia. Other topics, such as neuroscience and cognition, also potentially contribute significantly to explaining the psychology of the Indonesian people. With the updated aims and scope in mind, we encourage authors to explicitly address the impact of their work on the current state of propose improvements to existing practices. The editor and reviewers will specifically evaluate this discussion within the manuscript.